A CRITICAL ASSESSMENT OF THE INTRODUCTION OF PROPORTIONAL ANALYSIS BY THE SOUTH AFRICAN COURTS IN CIVIL-FORFEITURE JURISPRUDENCE - Nkululeko Christopher Ndzengu; John C von Bonde (Obiter, 2021)
This article deals with civil forfeiture in terms of the Prevention of Organised Crime Act1 (POCA) and considers the jurisprudential development of the instrumentality and exclusion analyses, considering in particular the newly introduced and limiting thirdstage, namely proportionality analysis. South African courts, appreciating the objectives of civil forfeiture, have utilized the Constitution to cushion its effects on property and liberty rights by implementing the proportionality analysis as a third criterion. The article also considers the call made by certain authorities that existing legislation ought to be amended in order to codify extant judicial precedent in this regard. In conclusion, it is recommended that civil forfeiture in South Africa should continue along the lines of the three-staged approach that has crystallized in practice by applying an approach incorporating instrumentality, exclusion and proportionality analyses.